Identification on the compressive strength of stabilized compacted soil by using traditional admixture as alternative material in industry / Mohd Mawardi Mohd Kamal, Normadiana Mohammad Hanapi and Mohd Amzari Yaccob - Mohd Kamal, Mohd Mawardi; Mohammad Hanapi, Normadiana; Yaccob, Mohd Amzari (2014)
Soil is a complex material composed essentially of clay minerals and sand with organic and associated minerals which influence soil properties. The purpose of this study is to identify the soil as the alternative raw materials in construction by replacing concrete in retaining walls or foundation. The material that been used in this study were categorized as the main groups of crystalline materials that is residual soil, which are categorized in kaolinite group. Besides that, this material was stabilized using the traditional admixture which was lime and its properties were improved using the compaction method to produce the optimum compressive strength of soil. The compaction method used was the Standard Proctor Test, and the results from the unconfined compressive strength test showed that the compressive strength before and after using the stabilization admixture. The percentage of admixture was determined by the dry weight of residual soil that been used in this test. It also illustrated that residual soil has a potential to contact with cold-formed steel column after being stabilized with traditional admixture which is lime.